Trump’s Anti-immigration Policies and Their Impacts on Latinos - BOUGRINE Sara; REKIK Fatima Zahra; ARIBI, Brahim (Faculty of Letters and Foreign Languages Department of English, 2019)
After the election of the American president Donald Trump, the political arena had witnessed a rapid change not just inside America, but also all over the globe. Immediately after he took office, Trump was determined to keep his promises of his presidential campaign of keeping America free from illegal immigration, “America is not an immigrants camp” Trump said. The consequences of that decision were frightening. Suddenly, families were torn apart and children were separated from their parents. Immigrants who considered themselves as American citizens now are being called outsiders, criminals and causing a danger to USA. In this thesis we want to examine the deep effects of Trump’s decision and how it changed the immigrants lives specially Latin-Americans. Furthermore, this research aims to reveal the amount of struggle and suffering of Latinos both socially and psychologically because of Trump’s anti-immigration policies, and how these recent policies changed Latinos’ lives and touched one of the important pillars of the society which is family